(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The paper investigates the problems related to the protection of the health of immigrants, specifically addressing the issues concerning the accessibility and usability of social and health services by migrant populations. From this perspective, therefore, the analysis focuses on examining the many obstacles which, in favor of these people, still stand in the way of an effective enjoyment of the services in question.